Enhancing Children's Digital Literacy Through Schoology-Based Hybrid Project-Based Learning - Solissa, Everhard Markiano; Hiola, Siti Fatimah; Santosa, Tomi Apra; Sukini, Sukini; Nugraha, Aat Ruchiat; Nurtamam, Mohammad Edy (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the effect of schoology-based hybrid project-based learning on digital literacy in children. This research is a type of quantitative research with a meta-analysis approach. The data of this study comes from the analysis of 25 studies obtained from ERIC, Sciencedirect, IEEE, Scopus and ProQuest. The inclusion criteria in the study are the research published in 2021-2024; SINTA or Scopus indexed research; Research should be relevant; The research data must be complete, and the sample size > 30 children. Data analysis with the help of JASP 0.19.30 application. The results of this study concluded that the average value of the summary effect size was ( rRE = 0.989; Z = 8.213; p < 0.001). These findings show a positive influence of schoology-based hybrid project-based learning on digital literacy in children.